Immunosuppressive therapies after intestinal transplant modulate the expression of Th1 signature genes during acute cellular rejection. Implications in the search for rejection biomarkers. (26th November 2014) - Zambernardi, Agustina; Chiodetti, Ana; Meier, Dominik; Cabanne, Ana; Nachman, Fabio; Solar, Héctor; Rumbo, Carolina; Gondolesi, Gabriel E.; Rumbo, Martin
Abstract Background and Aims Acute cellular rejection (ACR) and infections are leading causes of graft loss and death in intestinal transplant patients. Our aim was to evaluate the impact of maintenance immunosuppressive therapies on the expression of pro‐inflammatory mediators in small bowel at ACR diagnosis. Materials and Methods We analyzed expression levels of Th1‐associated genes, IFNG, CXCL10, and CXCL11 by qPCR in 46 selected graft biopsies unequivocally assigned to mild ACR (n = 14) or normal histopathology and clinical condition (n = 32) from 15 patients receiving two different immunosuppressive (IS) schemes. Double treatment: corticosteroids and tacrolimus (n = 17) and triple treatment: sirolimus or mycophenolate mofetil in addition to the basal therapy (n = 29). Results IFNG, CXCL10, and CXCL11 were induced during rejection (p < 0.05; p < 0.005, and p < 0.05, respectively). However, when rejection and control groups were classified according to immunosuppressive treatment, in the rejection group, significant differences of IFNG, CXCL10, and CXCL11 expression (p < 0.001; p < 0.005, and 0.01, respectively) were detected, whereas no differences were observed in the control group. Conclusion Gene expression of Th1 response mediators is higher during ACR. Triple IS group showed significantly lower expression of pro‐inflammatory Th1 mediators during mild ACR indicating that use of these markers to monitor rejection can be affected by the IS treatment used.